2013
DOI: 10.1021/cb4005518
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Properties Are a Key Determinant of the Size and Shape of Self-Assembled Virus-Derived Particles

Abstract: Controlling the geometry of self-assembly will enable a greater diversity of nanoparticles than now available. Viral capsid proteins, one starting point for investigating self-assembly, have evolved to form regular particles. The polyomavirus SV40 assembles from pentameric subunits and can encapsidate anionic cargos. On short ssRNA (≤814 nt), SV40 pentamers form 22-nmdiameter capsids. On RNA too long to fit a T=1 particle, pentamers forms strings of 22-nm particles and heterogeneous particles of 29 to 40 nm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 44 publications
4
79
0
Order By: Relevance
“…To understand the effect of perturbing parameters from these optimal values, in vitro assembly products were characterized by electron microscopy (e.g. (76, 78, 98, 108, 109)) or SAXS (16, 17) as functions of subunit and RNA concentrations, subunit-subunit interactions (controlled by pH, ionic strength, and protein sequence), and subunit-polymer interactions (controlled by ionic strength and protein-RNA binding domains). In addition, several groups have performed Brownian dynamics simulations in which coarse-grained triangular or pentameric subunits assemble around flexible polyelectrolytes (49, 50, 99, 110112), semi-flexible polyelectrolytes (112), or model NAs (99).…”
Section: Capsid Assembly Around Nucleic Acids and Other Polyelectromentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the effect of perturbing parameters from these optimal values, in vitro assembly products were characterized by electron microscopy (e.g. (76, 78, 98, 108, 109)) or SAXS (16, 17) as functions of subunit and RNA concentrations, subunit-subunit interactions (controlled by pH, ionic strength, and protein sequence), and subunit-polymer interactions (controlled by ionic strength and protein-RNA binding domains). In addition, several groups have performed Brownian dynamics simulations in which coarse-grained triangular or pentameric subunits assemble around flexible polyelectrolytes (49, 50, 99, 110112), semi-flexible polyelectrolytes (112), or model NAs (99).…”
Section: Capsid Assembly Around Nucleic Acids and Other Polyelectromentioning
confidence: 99%
“…5D), triplets, and quadruplets. An early study likely also observed doublets, although the structures could not be confirmed (72) and recently doublet dodedecadron capsids were observed for assembly of SV40 capsid proteins around certain lengths of RNA (17). Simulations independently predicted the formation of doublets around polyelectrolytes with about twice the optimal length (49, 99, 114) (Fig.…”
Section: Capsid Assembly Around Nucleic Acids and Other Polyelectromentioning
confidence: 99%
“…Virus‐based nanoparticles and virus‐like particles (VLPs) that lack the viral genetic material required for replication are potential platforms for vaccine design . Simian virus 40 (SV40), which is a polyomavirus found in both monkeys and humans, can be induced to form differently sized icosahedral particles depending on the size and composition of the nucleic acid component (DNA or RNA) . Assembly assays with the SV40 VP1 protein and short (1.9 knt) ssRNA molecules produce 22 nm diameter VLPs that are smaller than mature virions.…”
Section: D Cryo‐tem Images Of Nanoparticlesmentioning
confidence: 99%
“…(a) Protein‐RNA nanoparticles (T = 1 polyomavirus SV40 VP1 virus‐like particles) 22 nm in diameters (arrows) and larger assemblies, scale bar, 50 nm. (Reprinted with permission from Ref . Copyright 2013 American Chemical Society) (b) Lipid‐based hexosome nanoparticles, scale bar, 50 nm.…”
Section: D Cryo‐tem Images Of Nanoparticlesmentioning
confidence: 99%
“…In vitro, SV40, and other polyomaviruses, VP1 pentamers can assemble into a broad array of structures from 20 nm T=1 capsids to 40 nm T=7 capsids to 40 nm diameter tubes 19, 20 . Different nucleic acid substrates yield a similar range of structures with relatively stiff dsDNA favoring T=7 particles 21, 22 . On ssRNA substrates, VP1 forms uniform 22 nm diameter T=1 virus-like particles (VLPs) under mild solution conditions (50 mM MOPS, pH 7.2, 125 mM NaCl) in the absence of cellular or external factors 23 .…”
mentioning
confidence: 99%